Design Of 75 Kw Asynchronous Motor For Electric Vehicle Applications - Ulu, Cenk; Komurgoz, Guven (Aperta, 2016)
In this study, the design of 75kW (continuous 50kW) squirrel cage induction motor for electric vehicle applications is presented. First, the main design constraints and performance criteria are determined. Depending on these constraints and criteria, computer aided design of the motor is performed. Then, the electrical, magnetic and performance analyses of the motor are performed. The analysis results show that the designed motor satisfies the desired power specifications and the design performance criteria.